2015
DOI: 10.1371/journal.pone.0142177
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Resistance to Powdery Mildew in Brassica napus (AACC) and Raphanus alboglabra (RRCC) by Trichoderma harzianum TH12

Abstract: Trichoderma harzianum TH12 is a microbial pesticide for certain rapeseed diseases. The mechanism of systemic resistance induced by TH12 or its cell-free culture filtrate (CF) in Brassica napus (AACC) and Raphanus alboglabra (RRCC) to powdery mildew disease caused by ascomycete Erysiphe cruciferarum was investigated. In this study, we conducted the first large-scale global study on the cellular and molecular aspects of B. napus and R. alboglabra infected with E. cruciferarum. The histological study showed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…It has been reported that some Trichoderma spp., can stimulate ISR in crops via signaling molecules, such as jasmonic acid (JA), ethylene (ET), and salicylic acid (SA), to plant diseases caused by biotrophic or necrotrophic pathogens, such as S . sclerotiorum , Erysiphe cruciferarum , Fusarium verticillioides and Botrytis cinerea [2, 1620]. …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that some Trichoderma spp., can stimulate ISR in crops via signaling molecules, such as jasmonic acid (JA), ethylene (ET), and salicylic acid (SA), to plant diseases caused by biotrophic or necrotrophic pathogens, such as S . sclerotiorum , Erysiphe cruciferarum , Fusarium verticillioides and Botrytis cinerea [2, 1620]. …”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma harzianum TH12 and its CF were identified as providing the most significant growth inhibition of the phytopathogen S . sclerotiorum , which reached 100% among 30 Trichoderma species [2, 16]. Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations